2009
DOI: 10.1002/mus.21281
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variation of the innervation of the flexor digitorum profundus muscle and its clinical implications

Abstract: In anterior interosseous nerve syndrome and ulnar neuropathy, paralysis or weakness of the flexor digitorum profundus (FDP) muscles has been shown to vary according to the degree of involvement of the median and ulnar nerves, respectively. We traced these nerves in 50 cadaveric specimens in which each FDP was completely separated. The specimens were classified into six anatomic and another six presumptive electromyography (EMG) types according to the innervation patterns of the entire and the proximal one-thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…The complexity and overlap of the innervation of the muscles of the hand is well known (29,30); using this technique prior to repair could better delineate functional and nonfunctional muscles, potentially allowing for more effective interventions. Vibration imaging could also be applied postoperatively to assess muscle function in a noninvasive fashion that would be complementary to electromyography and high-resolution anatomic imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity and overlap of the innervation of the muscles of the hand is well known (29,30); using this technique prior to repair could better delineate functional and nonfunctional muscles, potentially allowing for more effective interventions. Vibration imaging could also be applied postoperatively to assess muscle function in a noninvasive fashion that would be complementary to electromyography and high-resolution anatomic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, this technique may have application in identifying muscle function before surgical interventions such as for muscle or tendon transfers or nerve grafting to either the brachial plexus or more distal peripheral nerves innervating the hand in patients after trauma. The complexity and overlap of the innervation of the muscles of the hand is well known (29,30); using this technique before repair could better delineate functional and nonfunctional muscles, potentially allowing for more effective interventions. Vibration imaging could also be applied postoperatively to assess muscle function in a noninvasive manner that would be complementary to electromyography and high-resolution anatomic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the flexor digitorum profundus muscle, which is also involved in the thumb-little finger pinch grip force, while primarily innervated by the ulnar nerve, also receives some of its innervations through branches from the median nerve. 27 Oh et al 38 suggested that because the flexor digitorum profundus tendons expand to the index and little fingers, this muscle may be affected in lesions of the median or ulnar nerve. It is possible that patients might attempt to overcome the weakness associated with first-digit flexion by producing excessive forces that do not correlate with functional levels.…”
Section: Discussionmentioning
confidence: 99%
“…Stepwise regression analyses revealed that pain intensity, finger pinch grip force between the thumb and little finger, depression severity, and cervical ROM in lateral flexion away from the side of the symptoms were significantly associated with the score on the functional status subscale and, when combined, explained 38 …”
Section: Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation